Museu e animação cultural: uma análise das práticas de educação e difusão do Museu Mariano Procópio Juiz de Fora/MG (1980-1996) - Arthur Oliveira da Silva (2015)
This study aimed to analyze the activities at the Museum Mariano Procopio in Juiz de Fora, in the period 1980 - 1996, with the aim of better understanding how the museum operated in cultural animation practices over the years and the reflection regarding to capture public. The bibliographic guidelines were based - on the following areas: museum and cultural events. For this project, in order to better capture the essence of the institution were surveyed Annual Reports of MAPRO / JF (1980-1996) along with the newspapers Diário Mercantil (1980-1983),Minas Tribune (1984-1996) and Tribune Afternoon (1986-1990). In the research pathway will check the cultural entertainment strategies, which allowed a greater or lesser adherence of the public, that is, the relationship between the profile of the activities that influence the maintenance of the institution's memory. It resaltar that this period is of great importance since the MAPRO / JF undergoes a change of management. The institution which was previously managed in the family in the 1980s is assumed by third parties. This breakdown of the family link has certain changes in the paradigms of the institution, both in its physical aspect as in the educational aspect. Analyses of investigated data enabled further insight into the resources used by the institution to keep alive the memory of the subject to municipal and national levels. Thus, we consider - whether this research may enable new way of seeing the trajectory of MAPRO / JF, not being the point of arrival, but rather the starting point for other approaches.